PENGARUH PROMOSI, LOKASI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN WISATAWAN PADA PUSAT OLEH-OLEH BANI RAWI DI KABUPATEN TANAH DATAR - Dahliana Khamener, Reni Yuliviona, Reza Fabio Alkindi (MENARA EKONOMI, 2017)
This research analized the influence of promotion,location and brand image of Bani RawiSouvenir Shop toward on customer purchase decision. The technique of the sample collectionwas accidental sampling method, which were collected 138 respondents. The multiple regressionanalysis was used to conduct the hypothesis test on this research.The results of the researchshowed that: (1) Brand image significantly toward on Bani Rawi customer purchase decision. (2)Location positively influenced toward on Bani Rawi customer purchace decision. (3) brandimage not significanly influenced toward on Bani Rawi customer purchase decision.Keywords: Promotion, Location, Brand image , Customer purchasing decision